Repositioning accuracy of two different mask systems - 3D revisited: Comparison using true 3D/3D matching with cone-beam CT - Boda-Heggemann, Judit; Walter, Cornelia; Rahn, Angelika; Wertz, Hansjörg; Loeb, Iris; Lohr, Frank; Wenz, Frederik (International journal of radiation oncology, biology, physics, 2006)
Purpose: The repositioning accuracy of mask-based fixation systems has been assessed with two-dimensional/two-dimensional or two-dimensional/three-dimensional (3D) matching. We analyzed the accuracy of commercially available head mask systems, using true 3D/3D matching, with X-ray volume imaging and cone-beam CT. Methods and Materials: Twenty-one patients receiving radiotherapy (intracranial/head-and-neck tumors) were evaluated (14 patients with rigid and 7 with thermoplastic masks). X-ray volume imaging was analyzed online and offline separately for the skull and neck regions. Translation/rotation errors of the target isocenter were analyzed. Four patients were treated to neck sites. For these patients, repositioning was aided by additional body tattoos. A separate analysis of the setup error on the basis of the registration of the cervical vertebra was performed. The residual error after correction and intrafractional motility were calculated. Results: The mean length of the displacement vector for rigid masks was 0.312 +/- 0.152 cm (intracranial) and 0.586 +/- 0.294 cm (neck). For the thermoplastic masks, the value was 0.472 +/- 0.174 cm (intracranial) and 0.726 +/- 0.445 cm (neck). Rigid masks with body tattoos had a displacement vector length in the neck region of 0.35 +/- 0.197 cm. The intracranial residual error and intrafractional motility after X-ray volume imaging correction for rigid masks was 0.188 +/- 0.074 cm, and was 0.134 +/- 0.14 cm for thermoplastic masks. Conclusions: The results of our study have demonstrated that rigid masks have a high intracranial repositioning accuracy per se. Given the small residual error and intrafractional movement, thermoplastic masks may also be used for high-precision treatments when combined with cone-beam CT. The neck region repositioning accuracy was worse than the intracranial accuracy in both cases. However, body tattoos and image guidance improved the accuracy. Finally, the combination of both mask systems with 3D image guidance has the potential to replace therapy simulation and intracranial stereotaxy. (c) 2006 Elsevier Inc.